The Effectiveness of Sharia Insurance Dispute Resolution Mechanisms in Promoting Sustainable Development Goals - Muhammad Hendri Yanova (Scholar Center, 2025)
The growth of the sharia insurance industry in Indonesia has given rise to new legal challenges, particularly in the development of dispute resolution mechanisms that are consistent with both sharia principles and national legislation. Alternative Dispute Resolution methods, such as mediation and arbitration, are considered more appropriate than litigation due to the unique nature of contracts and legal relationships in Sharia insurance. This study aims to evaluate the effectiveness of dispute resolution in the practice of sharia insurance in Indonesia and to assess the extent to which the existing legal framework ensures justice, legal certainty, and compliance with Islamic legal principles. This research employs a normative juridical method, using both the statute approach and the conceptual approach, to examine the relevant positive laws and Islamic legal doctrines governing dispute resolution in Sharia-based financial transactions. The findings reveal that strengthening the Alternative Dispute Resolution mechanism in sharia insurance disputes not only enhances access to justice and legal certainty but also directly contributes to the achievement of Sustainable Development Goal 16, which promotes peace, justice, and strong institutions. This study underscores the importance of harmonizing national law and Sharia norms in building a dispute resolution system that is fair, effective, and sustainable